2015
DOI: 10.3892/ijmm.2015.2278
|View full text |Cite
|
Sign up to set email alerts
|

Aplasia Ras homologue member I overexpression inhibits tumor growth and induces apoptosis through inhibition of PI3K/Akt survival pathways in human osteosarcoma MG-63 cells in culture

Abstract: Aplasia Ras homologue member Ⅰ (ARHI), an imprinted tumor-suppressor gene, is downregulated in various types of cancer. However, the expression, function and specific mechanisms of ARHI in human osteosarcoma (OS) cells remain unclear. The aim of the present study was to assess the effect of ARHI on OS cell proliferation and apoptosis and its associated mechanism. In the study, ARHI mRNA and protein levels were markedly downregulated in OS cells compared with the human osteoblast precursor cell line hFOB1.19. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
(39 reference statements)
2
9
0
Order By: Relevance
“…Therefore, we considered that the downregulation of ARHI expression is mainly caused by hypermethylation of the ARHI promotor region, leading to loss of the ability to suppress cell survival in osteosarcoma cells. A recent study clarified the inhibitory role of ARHI in growth and its role in promoting apoptosis in osteosarcoma cells . We did not repeat showing the role of ARHI in cell viability and apoptosis in this study.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Therefore, we considered that the downregulation of ARHI expression is mainly caused by hypermethylation of the ARHI promotor region, leading to loss of the ability to suppress cell survival in osteosarcoma cells. A recent study clarified the inhibitory role of ARHI in growth and its role in promoting apoptosis in osteosarcoma cells . We did not repeat showing the role of ARHI in cell viability and apoptosis in this study.…”
Section: Discussionmentioning
confidence: 54%
“…A recent study clarified the inhibitory role of ARHI in growth and its role in promoting apoptosis in osteosarcoma cells. (19) We did not repeat showing the role of ARHI in cell viability and apoptosis in this study. However, we showed that knockdown of ARHI rescues cell viability and apoptosis following zebularine treatment, supporting the proposition that ARHI could inhibit osteosarcoma growth and induce apoptosis.…”
Section: Discussionmentioning
confidence: 70%
“…Previous studies have reported that miR-221 promotes tumor development, while ARHI is a tumor suppressor gene [Chen et al, 2011;Li et al, 2013b;Ye et al, 2015Ye et al, , 2016. We transfected miR-221 mimics and si-ARHI into GAS5-overexpressing MG-63 cells to investigate the role of miR-221 and ARHI on cell proliferation, migration, and EMT of osteosarcoma cells.…”
Section: Gas5 Suppresses Cell Proliferation Migration and Emt Via Regulating Mir-221 And Arhi Expression In Osteosarcoma Cellsmentioning
confidence: 99%
“…Caspase3 plays an irreplaceable role in cell apoptosis. Caspase3 can be activated by a variety of factors, and it is the main terminal shear enzyme in the process of cell apoptosis 26 , 27 . Taken together, these results indicated that Tec possesses effective antitumor activities against OS through activation of caspase apoptosis axis.…”
Section: Discussionmentioning
confidence: 99%